Contours of Urban Violence and Insecurity: Digital Media Technologies and Mitigation of Urban Violence Among Undocumented African Migrants in South Africa - Muswede, Thabiso (Frontiers in Sustainable Cities, 2022)
This is a qualitative exploratory investigation into the use of digital media technologies in the mitigation of security concerns among undocumented migrants in the informal settlements within urban South Africa. The article acknowledges that adaptation of migrants in new environments is generally compounded by a myriad of challenges most of which are linked to lack of access to government systems and social capital or survival networks. This is particularly applicable to the urban settings where rampant violent crime and insecurity concerns are often laced with outbursts of xenophobia which contribute to further uncertainties among migrants. Extensive literature review and social media theory are used to explore the potential for digital media tools to mitigate violence and insecurity among migrants. A piloted in-depth interview was used to collect data from undocumented immigrants based on a snowballed sample to saturation levels. Data were analysed thematically to generate themes from which study findings were derived. Study findings show that, undocumented migrants suffer inexplicable barrages of social injustice due to violent crime and other insecurity concerns largely because they are scared to report cases to law enforcement agents, who in turn arrest them for being illegal in the country. Subsequently, the advent of digital and social media, particularly WhatsApp helps them to create a survival network platform to provide a sense of security and foster collaborations that deal with their safety concerns, uncertainty, and support for victims of violent crime.